FRI0046 TCZ Attenuates Atherothrombosis through The Specific Inhibition of Netosis and Monocyte-Mediated Proinflammatory Activity. (15th July 2016) - Ruiz-Limon, P.; Barbarroja, N.; Ortega, R.; Perez-Sanchez, C.; Jimenez-Gomez, Y.; Abalos-Aguilera, M.C.; Arias de la Rosa, I.; Font, P.; Aguirre, M.A.; Castro, M.C.; Calvo, J.; Collantes-Estevez, E.; et al.
Abstract : Background: Inhibition of the interleukin IL6 receptor pathway by tocilizumab (TCZ) is an effective treatment for rheumatoid arthritis (RA). TCZ reduces atherosclerosis markers and improves endothelial function. In peripheral blood, TCZ increases the percentage of natural killer and regulatory T cells and decreases the number of inflammatory Th1/Th17 lymphocytes. Monocytes activation and neutrophil extracellular traps (NETs) are key players in the development of cardiovascular disease; however, the specific effect of TCZ on these cells has not been described yet. Objectives: To analyze the molecular changes (focused on monocyte and neutrophil abnormalities) underlying the beneficial effect of TCZ on atherosclerosis and endothelial dysfunction in rheumatoid arthritis. Methods: Fifteen RA patients received 162 mg/week subcutaneous TCZ as combined therapy. Endothelial function was measured through post occlusive hyperemia using Laser-Doppler. To analyze the specificity of TCZ, blood samples from 5 RA patients with high disease activity no taking TCZ was used to perform in vitro studies. Isolated monocytes and neutrophils were treated in vitro with IL6 and blocking FCRII plus TCZ for 18 and 6 hours, respectively. Oxidative stress markers in leukocytes were analyzed by flow cytometry. NETosis was measured through Sytox staining of DNA fibers. Myeloperoxidase (MPO) and neutrophil elastase (NE) were analyzed in neutrophils by flow cytometry. mRNA expression of peptidyl arginine deiminase (PAD4) was measured by RT-PCR. Percentage of low density granulocytes (LDGs) was analyzed through flow cytometry. mRNA expression of genes involved in monocyte activation, prothrombotic state, lipid uptake and insulin resistance was analyzed in monocytes through RT-PCR. Activation of intracellular pathways was analyzed in monocytes using pathscan intracellular signaling array. Expression of miRNAs was evaluated in plasma. Results: After 6 months of treatment, TCZ reduced clinical parameters of inflammation, autoimmunity and joint damage. Endothelial function was significantly restored. TCZ decreased peroxide and peroxinitrite levels in RA leukocytes, most significantly in monocytes and neutrophils. Percentage of LDGs was also reduced after treatment. TCZ in vivo treatment reduced the expression of MPO, NE and PAD4 in RA neutrophils. The generation of in vitro induced NETs was also inhibited by TCZ. The expression of inflammatory and prothrombotic molecules, genes involved in lipid uptake and cellular activation and insulin signaling and the activation of various intracellular pathways were modulated in monocytes after in vivo TCZ treatment. All these results were recapitulated after in vitro TCZ treatment of RA monocytes and neutrophils. Plasma levels of miRNA-223, miRNA-146 and miRNA-23, previously reported to be modified by anti-TNFalpha drugs, were also upregulated after TCZ treatment. Conclusions: TCZ improves endothelial dysfunction and atherothrombosis through the restoration of the oxidative status, inhibition of the monocyte prothrombotic and inflammatory profile and the generation of NETosis Acknowledgement: Funded by CTS7940, PI2013–0191, CP15/00158, PI15/01333 Disclosure of Interest: None declared